Nitrogen-fixation and phosphate-solubilization bacteria isolated from alluvial and latosol soil paddy field - IKHWANI IKHWANI; NONON SARIBANON; TATANG MITRA SETIA; ERNY YUNIARTI; Jumakir Jumakir (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ikhwani, Saribanon N, Setia TM, Yuniarti E, Jumakir. 2021. Nitrogen-fixation and phosphate-solubilization bacteria isolated from alluvial and latosol soil paddy field. Biodiversitas 22: 4722-4730. This study aims to isolate, select and identify molecular characterization of bacteria from alluvial and latosol soil paddy field. This study has been conducted from February-June 2020 in the Soil Biology Laboratory, ICALRRD, Bogor. Alluvial and latosol soil samples were selected from Pusakanagara and Muara experimental gardens, Muara district. The result showed that bacteria growth in N-free media was higher from latosol soil as compared to alluvial soil. The higher nitrogenase activity isolates, could form ethylene gas concentration 1.1.E + 09 µmol/mL/hours, 1.7.E + 09 µmol/mL/hours and 1.3.E + 09 µmol/mL/hours from  alluvial 6, latosol 4, and latosol 9.  Three isolates have great PSB performances, i.e. isolates No. 4.2, 2.1 and 2 could dissolve 14.398 mg l-1, 12.648 mg l-1 and 12.145 mg l-1 of phosphate, from latosol soil. The highest N-fixing and solubilization capacity identified by molecular characterization i.e latosol 4, 4.2 and alluvial 7.1, alluvial-1.11. The phylogeny analyzed the presence of bacterial isolates in two distinct groups. Latosol 3.1 and latosol 4.2 isolates clustered in the same as the genus Lysinibacillus bacteria. The Alluvial 7.1 bacterial isolate showed similarities by Fictibacillus sp. and alluvial 1.2 isolate showed similarities by the genus Bacillus sp.